The Pedagogical Concept of Student-Centred Learning in the Context of European Higher Education Reforms - Hoidn, Sabine (European Scientific Journal, ESJ, 2016)
The increasing gap between the demand and supply of graduates with high-level qualifications, i.e. tertiary attainment levels, has been a central driver for curricular higher education reforms in Europe. In the last decade, the Bologna Process has established curricular reforms; however, progress toward the implementation of the pedagogical concept of student-centred learning in European higher education has been rather slow. This paper reviews the current educational policy context within which European higher education institutions operate. Societal developments and trends as well as curricular reform efforts to facilitate a paradigm and culture shift from teacher-centred learning to student-centred learning are discussed. The paper further outlines major obstacles from the perspectives of faculty and students that continue to hinder the successful and widespread implementation of a student-centred learning approach in higher education practice.